2006
DOI: 10.4049/jimmunol.176.7.3950
|View full text |Cite
|
Sign up to set email alerts
|

Desiccating Stress Induces T Cell-Mediated Sjögren’s Syndrome-Like Lacrimal Keratoconjunctivitis

Abstract: Chronic dry eye syndrome affects over 10 million people in the United States; it is associated with inflammation of the lacrimal gland (LG) and in some cases involves T cell infiltration of the conjunctiva. We demonstrate that environmental desiccating stress (DS) elicits T cell-mediated inflammation of the cornea, conjunctiva, and LG, but not other organs in mice. The lacrimal keratoconjunctivitis (LKC) was mediated by CD4+ T cells, which, when adoptively transferred to T cell-deficient nude mice, produced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
329
3
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 320 publications
(360 citation statements)
references
References 18 publications
16
329
3
12
Order By: Relevance
“…We have previously reported that desiccating stress-induced lacrimal keratoconjunctivitis was mediated by CD4+ T cells and was mitigated by CD4+CD25+ natural regulatory T cells [9]. In this study, an increase in CD4+ T cells and CCR5+ cells was accompanied by a decrease in CD8+ T cells in the ocular surface epithelium and lacrimal gland, resulting in an increased CD4/CD8 ratio.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…We have previously reported that desiccating stress-induced lacrimal keratoconjunctivitis was mediated by CD4+ T cells and was mitigated by CD4+CD25+ natural regulatory T cells [9]. In this study, an increase in CD4+ T cells and CCR5+ cells was accompanied by a decrease in CD8+ T cells in the ocular surface epithelium and lacrimal gland, resulting in an increased CD4/CD8 ratio.…”
Section: Discussionsupporting
confidence: 50%
“…The effects of desiccating stress on salivary gland immunopathology in the NOD strain were not investigated in this study. Our group had previously reported that desiccating stress promoted development of auto reactive CD4+ T cells in BALB/c mice that were capable of producing lacrimal keratoconjunctivitis, but not salivary gland inflammation when adoptively transferred to nude mouse recipients [9].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10 In turn, inflammation may cause dysfunction or disappearance of the cells responsible for tear secretion or retention. 11 Hinokitiol is a natural component isolated from Chamaecyparis taiwanensis that exhibits antibacterial, antifungal, antiviral, antitumor, and insecticidal activities, with insignificant cytotoxicity. [12][13][14][15] Recent studies reported that Hinokitiol displayed a significant antiinflammatory activity in a series of cells through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%